Tari Bedhaya Ketawang: Refleksi Mitos Kanjeng Ratu Kidul dalam Dimensi Kekuasaan Raja Kasunanan Surakarta - Sulistyo Haryanti (Greget, 2010)
This article is an interpretation of Tari Srimpi through the analysis of symbols, according to Hinduism. The interpretation focuses on a discussion of how aesthetic power is established through the symbol of four dancers in Tari Srimpi. Usually discussions about the four Tari Srimpi dancers (referred to as: batak, gulu, dhadha, buncit) are about keblat papat lima pancer (four points and a centre), and four human characteristics (amarah, aluamah, supiyah, and mutmainah). This article attempts to discuss the symbol of the four dancers from another angle, formulated through Hinduism, which describes four human potentials through the figure of Panca Pandawa. Although Pandawa consists of five brothers, it is actually a symbol of four human potentials: (1) Puntadewa as a symbol of spirituality, (2) Werkudara as a symbol of attitude, (3) Arjuna as a symbol ofÂ  science, and (4) the twins Nakula-Sadewa as a symbol of skill.Keywords: Srimpi dance, Panca Pandawa, and human potential.